Determinant of Tax Aggressiveness: Gender Diversity as Moderator - RAHMAN, Huda Aulia; UTAMI, Wiwik (Archives of Business Research, 2021)
This research aims to analyze the effect of transfer pricing, profitability, capital intensity, and advertising expense on tax aggressiveness with gender diversity as a moderating variable. The population of this research is the manufacturing sector companies listed on the Indonesia Stock Exchange for 2017-2019. The research sample used is 98 companies in the manufacturing sector which were selected based on the purposive sampling method. The research method used is a quantitative method, with panel data regression analysis. The results of this research were that profitability had a positive effect on tax aggressiveness, the capital intensity had a negative effect on tax aggressiveness. In contrast, transfer pricing and advertising expenses did not affect tax aggressiveness. Gender diversity as a moderator was only able to moderate the effect of profitability on tax aggressiveness.